Impact of Participatory Forest Management Implementation on Forest Condition: A Case Study of Dinsho and Agarfa Districts Forest Reserves, Bale zone, Southeast Ethiopia - Umer Abdela (Journal of Agriculture and Environment for International Development)
Efforts to conserve forest resources have been significant; however, sustainable conservation cannot be achieved without the active involvement of local communities. Participatory Forest Management (PFM) is recognized as an effective strategy for the long-term conservation of Ethiopia's remaining natural forests, particularly in the Bale zone, where community participation is essential. Despite this, the impacts of PFM have not been thoroughly evaluated or documented. This study aims to assess the effects of PFM on forest conditions in selected areas of the Bale zone. The research compares three forests practicing PFM with three that do not. To gather insights on the perceived status of these forests, the study employed semi-structured interviews, focus group discussions, and field observations. These qualitative methods provided a comprehensive understanding of local community perspectives regarding forest health and management practices. Data on forest parameters were collected through systematic sampling, using transects lines at 250-meter intervals across 152 plots, ensuring an equal number of plots for both forest types. Key forest metrics, including diameter at breast height (DBH), tree height, and the number of seedlings and mature trees, were analyzed using Microsoft Excel and various diversity indexes. This quantitative analysis allowed for a robust comparison of forest health indicators between PFM and non-PFM areas. The findings indicate that forests managed under PFM exhibit higher average biodiversity indexes and a greater number of stems per hectare compared to non-PFM forests. Specifically, the average number of trees increased significantly in PFM areas from their initial years to 2018. Additionally, the mean basal area also showed substantial growth in PFM forests, indicating improved forest health and productivity. The study recommends expanding PFM initiatives to all forests in the Bale zone, including smaller patches. It also highlights the need to focus on regenerating seedlings, as they face pressure from animal browsing, which could hinder forest recovery and health. This research contributes valuable insights into the effectiveness of community-based forest management practices in enhancing forest conditions in the Bale zone.